Benzyl Cyanide Leads to Auxin-Like Effects Through the Action of Nitrilases in Arabidopsis thaliana - Urbancsok, János; Bones, Atle M.; Kissen, Ralph (Frontiers in Plant Science, 2018)
Plants within the Brassicales order generate glucosinolate hydrolysis products that can exert different biological effects on several organisms. Here, we evaluated the physiological effects of one of these compounds, benzyl cyanide (phenylacetonitrile), when exogenously applied on Arabidopsis thaliana. Treatment with benzyl cyanide led to a dose-dependent reduction of primary root length and total biomass. Further morphological changes like elongated hypocotyls, epinastic cotyledons and increased formation of adventitious roots resembled a severe auxin-overproducer phenotype. The elevated auxin response was confirmed by histochemical staining and gene expression analysis of auxin-responsive genes. Nitriles are converted by specific enzymes, nitrilases (NIT1-3), to their corresponding carboxylic acids. The nitrilase mutants nit1 and nit2 tolerated benzyl cyanide treatments better than the wild type, with nit2 being less resistant than nit1. A NIT2RNAi line suppressing several nitrilases was resistant to all tested benzyl cyanide concentrations. When exposed to phenylacetic acid -the corresponding carboxylic acid of benzyl cyanide- wild type and mutant seedlings were however equally susceptible and showed a more severe auxin phenotype than upon cyanide treatment. Here, we demonstrate that the auxin-like effects triggered by benzyl cyanide on Arabidopsis are due to its nitrilase-mediated conversion to the natural auxin phenylacetic acid.